Use of Canva Application as a Learning Media - Ilham, Seprian; Vazquez Cano, Esteban; Novita, Lolla (Al-Hijr: Journal of Adulearn World, 2022)
This study aims to determine the use of the Canva application as a medium for learning Arabic for class V Madrasah Ibtidaiyah Dharmasraya. The method that the researcher uses is a qualitative research method with a descriptive approach. Observing events and phenomena around and incorporating them into research results. The object of research is the fifth grade students of Madrasah Ibtidaiyah in Dharmasraya. The research was carried out for several days with the help of a teacher in the field of Arabic studies to facilitate research. During the research, the researcher found some minor problems, such as the noisy atmosphere of the class when the researcher was researching, the electricity went out when the researcher was presenting the learning media and several other minor problems. The results showed that the Canva application was suitable to be used as a learning medium for the fifth grade Arabic language study at Madrasah Ibtidaiyah Dharmasraya, with guidance from the study area teacher as an effort to understand students' understanding of Arabic learning materials at school. Hopefully with the Canva application as a supporting medium for learning Arabic, it can motivate educators to be more creative in carrying out learning.